Комплексна оцінка стану забруднення грунтів м. Маріуполь методом головних компонент - Жуков, М.Н.; Кураєва, І.В.; Войтюк, Ю.Ю.; Стахів, І.Р.; Буніна, А.Я.; Матвієнко, О.В. (Геоінформатика, 2015)
Проведено комплексну оцінку забруднення ґрунтів м. Маріуполь важкими металами. Рівень забруднення ґрунтів залишається високим, головним джерелом забруднення є підприємства чорної металургії. Встановлено, що найбільш техногенними металами є цинк і мідь. Для виявлення факторів, які впливають на забруднення ґрунтів, застосовано метод головних компонент. Проведена комплексная оценка загрязнения почв г. Мариуполь тяжелыми металлами. Уровень загрязнения почв остается высоким, главный источник загрязнения — предприятия черной металлургии. Установлено, что наиболее техногенными металлами являются цинк и медь. Для определения факторов, влияющих на загрязнение почв, применен метод главных компонент. Purpose. Iron and steel industry is the leading sector of the economy of Ukraine. But at the same time, the industry is a major polluter of the environment and its individual components. By the index of atmospheric pollution, the city of Mariupol of Donetsk region is the number one polluter in Ukraine. The aim of this study was to conduct a comprehensive ecological and geochemical study using modern approaches to eco geochemistry.
Design/methodology/approach. To determine the concentration factors to make an and ecogeochemical assessment of the total pollution index, we used the method of Yu.Yu. Sayeta. The estimation of the contamination of the soils was conducted using the method of M.N. Zhukov. The maps of the distribution of heavy metals in soils constructed using the program of MapInfo 9.
Findings. It found out that the soils of the investigated territory are mainly black earth soils. New data on the content of heavy metals obtained. It established that the halos of heavy metals scattering are not only around the enterprises, but also in the outskirts of the city. The largest concentrations of heavy metals observed at a distance of 1—2 km from the enterprises. Geochemical association of heavy metals in Mariupol soils includes such elements as Pb > Cu > Zn > Cr > Mn (range 0—5 cm), Pb > Cu > Cr > Mn > V (range 5—10 cm).
Practical value/ implications. The assessment of ecological and geochemical soil conditions of Mariupol by the total pollution index revealed that the soils have a high (dangerous) level of contamination. Using the method of principal components, we managed to identify the main factors that affect ecological condition of the soils.